Laser microvia formation in polyimide thin films for metallization applications - Roeger B. (2017)
Purpose - The purpose of this paper is to demonstrate laser microvia drilling of polyimide thin films from multiple sources before metallic sputtering. This process flow reduces Flexible Printed Circuit Board (FPCB) material, chemical and operational costs by 90 per cent in the construction of flexible circuits. Design/methodology/approach - The UV laser percussion drilling of microvias in 25mm thick polyimide films with low coefficients of thermal expansion (CTE) and elastic modulii was investigated. Results were obtained using Scanning Electron Microscopy and Surface Profilometry. Polyimide films tested included: Dupont™ Kapton® EN; Kolon® GP and LV; Apical® NPI; and Taimide™ TA-T. Findings - There was no direct relationship between the top and bottom diameters and ablation depth rates between the polyimide films tested using the same test conditions. There was a direct relationship with exit diameters and etch rates at different laser pulse frequency rates and fluence levels. Laser pulse rates at 30 kHz produced 20 per cent larger exit diameters than at 70 kHz, however at 70 kHz the first pulse etched 16.5 per cent more material. High fluence levels etched more material but with a lower etch efficiency rate. Other microvia quality concerns such as surface swelling, membrane residues on the bottom side and surface debris inside the microvias were observed. Nanoscale powder-like surface debris was observed on all samples in all test conditions. Originality/value - This is the first comparison of material specifications and costs for films from multiple polyimide manufactures and laser microvia drilling. The paper also is the first to demonstrate results using a JDSU™ Lightwave Q302® laser rail. The results provide the first insights into potential microvia membrane issues and debris characteristics. © Emerald Group Publishing Limited.